Local exhaust ventilation : aerodynamic processes and calculations of dust emissions - Logachev, Ivan Nikolaevich; Logachev, Konstantin Ivanovich, 1968-; Averkova, Olga (CRC Press, 2016)
Control Harmful Emissions and Improve Work ConditionsLocal Exhaust Ventilation: Aerodynamic Processes and Calculations of Dust Emissions examines how emissions inherent to production processes in the metal, mining, chemical, and other industries can adversely affect the workplace by compromising a worker's health and/or contributing to the deterioration of equipment quality and performance. Professionals concerned with the aerodynamics of dust control ventilation, particularly at industrial plants, can greatly benefit from this book. This text considers the impact of emissions exposure to occupational safety and health and the environment, explores the practical purposes of industrial ventilation, and outlines how local exhaust ventilation can help control the emission of harmful substances in industry.